Savage Systems: Colonialism and Comparative Religion in Southern Africa - Chidester, David (University Press of Virginia, 1996)
Savage Systems examines the emergence of the concepts of "religion"and "religions" on colonial frontiers. The book offers a detailed analysis of the ways in which European travelers, missionaries, settlers, and government agents, as well as indigenous Africans, engaged in the comparison of alternative religious ways of life as one dimension of intercultural contact. Focusing primarily on ninteenth-century frontier relations, David Chidester demonstrates that the terms and conditions for comparison–including a discrouse about "otherness" that were established during this period still remains. A volume in the series Studies in Religion and Culture
Keywords: History / Africa / South / General; Religion / Philosophy